FUNGSI KADERISASI DALAM MENINGKATAN KUALITAS KEPEMIMPINAN - Muhammad Rizki Syahputra, T. Darmansah (CV. Pusdikra Mitra Jaya, 2020)
The purpose of this study was to determine the function of regeneration in improving leadership quality. In this study, using the library research method (library research) by collecting a number of books, magazines, journals, lifet relating to the problem and research objectives. Collecting data with the results of previous research which support data on research themes related to leadership regeneration and leadership quality with the research process starting with the stages of identifying, finding relevant information, analyzing the findings, and then developing and expressing them into new findings related to the regeneration function in improving leadership qualities. The results of this study found that, 1) Informal cadre, 2) formal cadre. A good leader is not seen by how many followers he has, and how long he leads, but by how much he can create new leaders. Leadership refers to a process to move a group of people towards a predetermined goal by encouraging them to act in a non-coercive manner. Thus, it can be said that leadership is a role and also a process for influencing others. Whereas a leader is a member of an association who is given a certain position and is expected to act according to his position. A leader is someone in an association who is expected to be able to use his influence in realizing and achieving group goals accompanied by full honesty. An honest leader is someone who leads and not someone who uses his position to lead.